2013
DOI: 10.1371/journal.pone.0074719
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ovariectomy on Calcium Homeostasis and Myofilament Calcium Sensitivity in the Aging Mouse Heart

Abstract: This study determined whether deficiency of ovarian estrogen starting very early in life promoted age-associated Ca2+ dysregulation and contractile dysfunction in isolated ventricular myocytes. Myocytes were isolated from anesthetized C57BL/6 female mice. Animals received an ovariectomy or sham-operation at one month and were aged to ~24 months. Excitation-contraction coupling parameters were compared in fura-2 loaded myocytes (37°C). While Ca2+ transients were larger and faster in field-stimulated myocytes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…If we use an in vitro calibration curve to convert our data to Ca 2ϩ concentration, peak Ca 2ϩ transients are ϳ70 nM in proestrus, metestrus, and diestrus compared with ϳ90 nM in estrus. These values are comparable with those previously reported by our group and others who have used in vitro calibration curves to investigate Ca 2ϩ handling in myocytes from female rodents (e.g., 14,20,66). By contrast, with a similar calibration approach, peak transients are much larger in myocytes from male rodents (e.g., 15,50,56,57).…”
Section: Discussionsupporting
confidence: 90%
“…If we use an in vitro calibration curve to convert our data to Ca 2ϩ concentration, peak Ca 2ϩ transients are ϳ70 nM in proestrus, metestrus, and diestrus compared with ϳ90 nM in estrus. These values are comparable with those previously reported by our group and others who have used in vitro calibration curves to investigate Ca 2ϩ handling in myocytes from female rodents (e.g., 14,20,66). By contrast, with a similar calibration approach, peak transients are much larger in myocytes from male rodents (e.g., 15,50,56,57).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, oestrogen increased expression of NCX, while it was decreased in OVX rats . However, in other studies, no change was observed in the expression of NCX expression in both oestrogen treatment and OVX animals . Although oestrogen decreased the expression of PLB, and OVX increased its expression, no change in expression was found in other reports .…”
Section: Ers and βArs As Coregulators Of Cardiac Ca2+‐handling Proteinsmentioning
confidence: 69%
“…Similarly, studies examining the role of oestrogen on the expression of LTCC yielded mixed results. Oestrogen decreased LTCC protein levels in rat ventricular myocytes (RVMs), while OVX increased its expression in RVMs, but decreased its expression in mouse ventricular myocytes …”
Section: Ers and βArs As Coregulators Of Cardiac Ca2+‐handling Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, NCX expression was increased by E 2 and was decreased in untreated OVX rats (93). In other studies, no change was observed in the expression of NCX expression by estrogen treatment or OVX (25,94). Kravtsov et al (76) determined NCX activity in the heart from OVX rats.…”
Section: Estrogen and The Na + /Ca 2+ Exchangermentioning
confidence: 99%